PENGARUH SPESIALISASI TUGAS DAN GAYA KEPEMIMPINAN TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. PLN CABANG BATURAJA - Syafe’i, Darman (Universitas muhammadiyah palembang, 2018)
This Study aims to determine the effect of task specialization and leadershipstyle on te effectiveness of employees at PT. PLN Baturaja. The analysisused is multiple linear regression analisys, t-test, F tes and coefficientdetermination. The results of the analysis indicate that the specialization oftask and leadership styles affect the effectiveness of empoloyees at PT.PLN Baturaja either partially or simultaneously. The magnitude of thecoefficient of determination ( R ) specialization of task and influenceleadership style by 30,20 % againt t he effectiveness of employees whilethe remaining 69,80 % influenced or varied by other variables. Reseacherssuggested that companies that consestently implement task specializationof employees and improving leadership style through a brefing that theemployee is willing to improve the effectiveness of its work.